Vibrations Investigateof Octahedral Hexahalogeno-anions (INTERNATIONAL JOURNAL OF APPLIED SCIENCE & TECHNOLOGY, 2018)
The vibrational constants of vibration have been computed for the octahedral hexa-halogeno anions of the metals of VIII group using latest vibrational wavenumbers. Three modified force fields such as GVFF, MUBFF and MOVFF are selected to compute the force constants. The mean amplitudes of vibrations are investigated at three temperatures. The trends among the force constants are examined and the results are logically discussed and some useful conclusions are drawn.